Prenatal and clinical characteristics of pregnant women infected with COVID-19 in Yazd, Iran: A multicenter cross-sectional study - Razieh Sadat Tabatabai; Leila Asadi; Maryam Mohammadi; Mina Rahmani; Elahe Rezaeian; Fatemeh Ghasemi; Mohammad Javad Tarahi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Coronavirus infection has caused widespread concern among mothers and physicians about the health of pregnant women and infants. Objective: The aim of this study was to evaluate the clinical and prenatal findings of pregnant women with coronavirus disease-2019 (COVID-19) virus. Materials and Methods: The present study was a descriptive study that was conducted in 6 mother and child care centers. In this study, 81 pregnant women with COVID-19 admitted to centers in the period from March 2020-September 2020 were studied. Clinical and prenatal findings of the pregnant mothers were recorded using a data collection form with details of demographic characteristics and these were analyzed. Results: The gestational age of the affected women was between 4 and 40 wk. 48 deliveries were performed and 25% of deliveries were preterm. Coronavirus infection was the cause of termination of pregnancy in 4 cases. The most common symptoms of women when visiting the medical centers were: dry cough (58.0%), muscle pain and myalgia (56.8%) and fever (51.9%). The most common laboratory findings in the women were: increased C-reactive protein (67.90%), lymphopenia (18.51%), decreased white blood cells (27.16%), and increased liver enzymes (18.51%). Regarding the status of the newborns, out of the 33 neonates examined, 3 neonates were diagnosed with COVID-19. Conclusion: The most common symptoms of pregnant women with COVID-19 are similar to those of other adults. In relation to neonatal infection, given that a number of the neonates tested positive, there appears to be evidence of vertical transmission, which requires further investigation.